2020
DOI: 10.3390/cancers12092536
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Patients with Signet Ring Subtype of Colorectal Cancer with Peritoneal Metastasis Treated with CRS & HIPEC

Abstract: Signet ring cell subtype (SRC) of colorectal cancer (CRC) is a rare subtype and occurs in approximately 1% of all patients with CRC. Patients with peritoneal metastasis (PM) of SRC have a poor prognosis, and this subtype is frequently considered as a contra-indication for extensive surgical treatment. This retrospective study from two dedicated peritoneal surface malignancy centers in Japan included all patients treated with CRS ± hyperthermic intraperitoneal chemotherapy (HIPEC) between July 1994 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…As for CRC with PM, it has been reported that cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is beneficial for selected patients [ 85 ]. However, properly selecting candidates who may benefit from this treatment is very important.…”
Section: Treatmentmentioning
confidence: 99%
“…As for CRC with PM, it has been reported that cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is beneficial for selected patients [ 85 ]. However, properly selecting candidates who may benefit from this treatment is very important.…”
Section: Treatmentmentioning
confidence: 99%
“…The combination of CRS and HIPEC has yielded a 30% to 50% 5-year survival rate for well-selected patients 3,4 compared with a 5-year survival rate lower than 10% under modern chemotherapy. 5 However, major morbidity is reported to be in the range of 30% to 45% of cases, even in specialized centers, [6][7][8] and about 30% of patients sustain early (\ 12 months) recurrence. [9][10][11] In an attempt to optimize surgical results, various prognostic factors have been proposed to aid in patient selection for this complicated procedure that includes completeness of cytoreduction, intraabdominal tumor burden as measured by the Peritoneal Carcinomatosis Index (PCI), tumor clinical presentation, and histologic characteristics.…”
mentioning
confidence: 99%